Agrarökonomische Lehre zwischen wissenschaftlichem Anspruch und gesellschaftlicher Relevanz; Teaching Agricultural Economics - Scientific Claims and Demands of Society - Dieter Kirschke (German Journal of Agricultural Economics (GJAE), 2019)
– Teaching agricultural economics widely reflects new research developments providing analytical competence. However, does teaching also give orientation on current and relevant demands of society, encouraging and sharpening the assessment capacity of students on such questions? There are doubts. In this paper we sketch out some deficits and address some possible reasons. A basic problem is a widespread critical view on economic thinking in public debates that does not stop at the lecture hall. Though, there are home-made problems, too. We suggest a stronger focus on the normative economic toolbox and its use for demands of society. More suggestions: despite all specialisation not to forget basic economic concepts; to encourage the critical dispute on topics and positions; and to accentuate normative questions.
Keywords: 330